Does planning before writing help? Options for pre-task planning in the teaching of writing. (11th September 2021) - Ellis, Rod
Abstract: An important issue in the teaching of writing is whether students should prepare a plan before they start writing. Teacher guides generally recommend pre-task planning (PTP) but with provisos. Research that has investigated PTP, however, does not lend unconditional support to PTP. This article takes a look at the research and draws from it a number of options that teachers of L2 writing can consider when deciding whether and how to undertake PTP in their own teaching context.